2016
DOI: 10.1261/rna.056168.116
|View full text |Cite
|
Sign up to set email alerts
|

Influence of two bulge loops on the stability of RNA duplexes

Abstract: Fifty-three RNA duplexes containing two single nucleotide bulge loops were optically melted in 1 M NaCl in order to determine the thermodynamic parameters ΔH°, ΔS°, ΔG°, and T for each duplex. Because of the large number of possible combinations and lack of sequence effects observed previously, we limited our initial investigation to adenosine bulges, the most common naturally occurring bulge. For example, the following duplexes were investigated: 5'GGCAXYAGGC/3'CCG YX CCG, 5'GGCAXY GCC/3'CCG YXACGG, and 5'GGC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 72 publications
0
2
0
Order By: Relevance
“…b B stands for dsRNA with bulge loop, and I stands for dsRNA with internal loop. c The experimental data are from(74)(75)(76)(77)(78)(79)(80).dsRNA Structure, Stability & Flexibility Biophysical Journal 115, 1403-1416, October 16, 2018 1411…”
mentioning
confidence: 99%
“…b B stands for dsRNA with bulge loop, and I stands for dsRNA with internal loop. c The experimental data are from(74)(75)(76)(77)(78)(79)(80).dsRNA Structure, Stability & Flexibility Biophysical Journal 115, 1403-1416, October 16, 2018 1411…”
mentioning
confidence: 99%
“…The current set of RNA folding parameters are enumerated in the nearest neighbor database (NNDB), along with examples of their use (Turner and Mathews 2010). Subsequent to the determination of the latest set of Turner rules, a number of optical melting experiments have demonstrated that improvements in the nearest neighbor parameter models and values are possible (Huynen et al 1997;Znosko et al 2002;Chen et al 2004Chen et al , 2005Chen et al , 2009Chen et al , 2012Vecenie and Serra 2004;Bourdelat-Parks and Wartell 2005;O'Toole et al 2005O'Toole et al , 2006Vecenie et al 2006;Wilkinson et al 2006;Badhwar et al 2007;Blose et al 2007;Davis and Znosko 2007Shankar et al 2007;Carter-O'Connell et al 2008;Znosko 2008, 2009;Clanton-Arrowood et al 2008;Miller et al 2008;Nguyen and Schroeder 2010;Sheehy et al 2010;Thulasi et al 2010;Liu et al 2011;McCann et al 2011;Hausmann and Znosko 2012;Lim et al 2012;Vanegas et al 2012;Kent et al 2014;Murray et al 2014;Kwok et al 2015;Strom et al 2015;Tomcho et al 2015;Crowther et al 2017;Phan et al 2017).…”
Section: Introductionmentioning
confidence: 99%